Recreation on the Wichita Riverfront: activating the Arkansas River a recreational greenway - Simon, Christopher (Kansas State University, 2011)
Riverfronts and greenways are our retreat to nature within the urban setting. They provide connections, opportunity for recreation, habitat for flora and fauna, and most importantly spaces that encourage exercise and social interaction. When these areas are located within the urban context, they are especially susceptible to the degradation that comes with the development of an area such as pollution, erosion, and in some cases lack of care or maintenance. The riverfront in Wichita suffers from three hindrances that restrict it from becoming an asset to the community and compromises human and ecological health along the river. Limited accessibility, a lack of recreational amenities, and poor environmental quality all contribute to the river being under-utilized. While these three elements compromise the site, the location makes it a prime candidate for transformation, creating a cohesive riverfront that has great potential to be utilized by the residents of a quickly growing downtown area. Through the establishment of these dilemmas a framework that focuses on the access and awareness, recreational amenities, and corridor enhancement can then be applied to the Wichita Riverfront. The Wichita Riverfront will encompass active and passive recreation that promotes human health through exercise, social interaction, and improved ecological conditions.
Keywords: Wichita; Riverfront; Recreation; Landscape Architecture (0390)